Pedagogical Support of Foreign Students’ Sociocultural Adjustment: The Experience of Implementation - G. P. Ivanova; O. K. Logvinova; N. N. Shirkova (Высшее образование в России)
This article addresses the problem of pedagogical support within the process of foreign students’ sociocultural adjustment. Scientific interest to this theme is caused by the processes of  internationalization of higher education, the need to solve new tasks coming from intensification and expansion of international educational contacts. The authors specify the concept “pedagogical support” as applied to sociocultural adjustment of foreign students and characterize it in relation to interaction of different resources (personal, institutional, environmental). The paper distinguishes and describes criteria and the levels of foreign students’ sociocultural adjustment. Special attention is paid to the factors complicating the process of pedagogical support. The article analyzes the experience of the authors’ program “The Foreign Student in the Russian Higher Education Institution” implementation. The presented pedagogical techniques promoted the increase of foreign students’ level of sociocultural adjustment. The authors have experimentally confirmed the efficiency of the developed program and reasoned the conditions of its successful implementation: organizational and pedagogical promoting the development of various forms of socially important activities in the multicultural environment of higher education institution; methodical reflecting teachers’ and staff readiness to develop the process; administrative, acting as a consistent system of pedagogical interaction organization. The results obtainedcan serve as a basis for justification and actualization of  technological approach in the process of sociocultural adjustment of foreign students at various levels of higher education.